Study of the Involvement of Phosphatidic Acid Formation in the Expression of Wound‐Responsive Genes in Cotton. Issue 6 (10th September 2018) - Bourtsala, Angeliki; Dafnis, Ioannis; Chroni, Angeliki; Farmaki, Theodora; Galanopoulou, Dia
Abstract: Plants use phospholipase D (PLD, EC 3.1.4.4)/phosphatidic acid (PtdOH) for the transduction of environmental signals including those coming from wounding. Based on our previous findings suggesting that wound‐induced PLDα‐derived PtdOH can act as a local signaling molecule in cotton ( Gossypium hirsutum ), we show that wounding immediately increases local NADPH oxidase (NADPHox) and cellulose synthase A (CeSA) gene expression. After developing a novel fluorimetric assay for the investigation of n‐butanol inhibitory effect on PLD activity, we show that only NADPHox gene upregulation is reduced when n‐butanol is applied prior to wounding. This suggests that NADPHox is a possible downstream target of PLD function, while a different CeSA‐involving response system may exist in cotton. Overall, this study provides new knowledge on signal‐transduction mechanisms following wounding of cotton leaves.